Different Roles of Teachers in the ELT Classroom - Poudel, Nab Raj (Journal of NELTA Karnali, 2022)
This article explores the expected roles of language teachers in an ever-shifting English language teaching scenario. It introduces the traditional roles of language teachers and goes on to discover new roles evolved because of the new theories and innovations in this field. While analysing and interpreting, I reviewed the related literature on the concerned topic to review the roles of English language teachers in the language classroom. After the systematic thematic review of the literature, I, as part of the findings, concluded that the language teachers’ roles are always evolving and bend towards consenting autonomy to the learners for providing them more control over their own learning. The roles assumed by the teachers are that of a facilitator, an assessor, a manager, a guide, a resource provider, a digital enthusiast, a cultural diplomat, and many others. A language teacher should be smart and flexible enough to morph into various roles as per the context and needs of the teaching-learning situation in the classroom. There is a continual need of exploring more plausible roles which can expedite language learning in more systematic and organized yet effective ways.